2020
DOI: 10.1080/09593985.2020.1757264
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-shortwave diathermy - a new purported treatment for management of patients with COVID-19

Abstract: The pandemic spread of coronavirus disease 2019 has driven efforts to address the global threat to public health and there is increasing pressure to exploit interventions to manage the pneumonic inflammation manifested in this disease. Ultra-shortwave diathermy (USWD) is proposed by some rehabilitation professions in China, purportedly to minimise pneumonic inflammation. However, treatment of any symptomatic pneumonia should be evidence-based. There is no valid evidence, published in English, which establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…The application of Curapulse 970™ shortwave diathermy machines and two Radarmed 950+™ microwave machines was performed, and the results were promising for COVID-19 treatment. The treatment session involved the application of the USWT electrode on the anterior and posterior parts of the trunk for 15 m/d till patient discharge [ 55 ]. A review of the biological effects of shortwave concluded that based SW has fewer side effects and more benefits, but they also require further research on the side effects [ 56 ].…”
Section: Rehabilitationmentioning
confidence: 99%
“…The application of Curapulse 970™ shortwave diathermy machines and two Radarmed 950+™ microwave machines was performed, and the results were promising for COVID-19 treatment. The treatment session involved the application of the USWT electrode on the anterior and posterior parts of the trunk for 15 m/d till patient discharge [ 55 ]. A review of the biological effects of shortwave concluded that based SW has fewer side effects and more benefits, but they also require further research on the side effects [ 56 ].…”
Section: Rehabilitationmentioning
confidence: 99%
“…6,7,8,9 Suggestions have also been made that supportive therapies such as ultra-short-wave diathermy (USWD) perform functions to boost the immune responses and inhibit inflammation. 10,11,12,13…”
Section: Introductionmentioning
confidence: 99%
“…USWD has been used in the field of physical therapy and rehabilitation for many decades 14,15,16 , but the evidence for its application as part of the COVID-19 management is debatable. 10 During the outbreak of severe acute respiratory syndrome (SARS), USWD was widely employed by rehabilitation professionals in China to reduce pneumonia inflammation. Zhang et al evaluated the efficacy of both USWD and conventional therapy in 38 patients with SARS, where USWD was used as an adjuvant treatment in addition to standard therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Ultra-short wave diathermy therapy (USWD) is one of the oldest forms of electrotherapeutic modality traditionally used by physical therapists to treat various inflammatory diseases. Many studies have demonstrated that USWD is capable of relieving the inflammation and has been suggested as promising adjuvant to drug-based therapies [15]. The beneficial effects of USWD in ALI patients were also reported, however, the mechanisms underlying these effects are still largely unknown.…”
mentioning
confidence: 99%
“…The physiological effects attributed to USWD include increased regional blood flow, decreased soft tissue pain and stiffness, reduced inflammation, relieved edema, and healed wounds, which are probably a result of the ability of cells to absorb energy from oscillating electrical fields of defined frequencies and/ or amplitudes [11]. Due to anti-inflammatory property of USWD, its application for the treatment of ALI patients has increased dramatically in the last 20 years [15]. The pathophysiological process of ALI is recognized as an excessive, uncontrolled inflammatory response in the lungs.…”
mentioning
confidence: 99%